Safety of frozen and dried forms of whole yellow mealworm (Tenebrio molitor larva) as a novel food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Torsten Bohn; Montaña Cámara; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; Ángeles Jos; Alexandre Maciuk; Inge Mangelsdorf; Breige McNulty; Androniki Naska; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the safety of frozen, dried and powder forms of whole yellow mealworm (Tenebrio molitor larva) as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The term yellow mealworm refers to the larval form of the insect species T. molitor. The NF consists of the frozen and dried forms of the whole yellow mealworm. The frozen form mainly consists of water, crude protein, carbohydrates and fat, whereas the dried forms consist of crude protein, fat and carbohydrates. The Panel notes that the levels of contaminants in the NF highly depend on the occurrence levels of these substances in the insect feed. The Panel notes that there are no safety concerns regarding the stability of the NF if the NF complies with the proposed specification limits during its entire shelf life. The NF has a protein content that ranges between 13 and 48 g/100 g. The Panel acknowledges that the true protein content is overestimated when using the nitrogen‐to‐protein conversion factor of 6.25 due to the presence of non‐protein nitrogen from chitin. The applicant proposed to use the NF as food ingredient in various food products. The target population proposed by the applicant is the general population. Considering the composition of the NF and the proposed conditions of use, the consumption of the NF is not nutritionally disadvantageous. The Panel notes that no safety concerns arise from the toxicological information of the NF. The Panel considers that the consumption of the NF might trigger primary sensitisation to yellow mealworm proteins and may cause allergic reactions in subjects allergic to crustaceans, dust mites and molluscs. Additionally, allergens from the feed may end up in the NF. The Panel notes that allergic reactions may occur upon consumption. The Panel concludes that the NF is safe under the proposed uses and use levels.